TÌNH HÌNH NHIỄM GIUN SÁN Ở CÁ THIA ĐẦU SỌC (Dascyllus reticulatus Richardson, 1846) VÀ CÁ THIA BA ĐỐM TRẮNG (Dascyllus trimaculatus Ruppell, 1829) KHU VỰC VỊNH NHA TRANG, TỈNH KHÁNH HÒA - Võ, Thị Hà; Lê, Thị Kiều Oanh; Nguyễn, Thị Hải Thanh; Nguyễn, Thị Phương Liên (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
THE SITUATION OF HELMINTH INFECTIONS IN Dascyllus reticulatus (Richardson, 1846) AND Dascyllus trimaculatus (Ruppell, 1829) IN NHA TRANG BAY, KHANH HOA PROVINCEThe survey was carried in Nha Trang bay, Khanh Hoa province from June to November 2018, a total of 275 samples of Dascyllus (155 individuals of D. reticulatus and 120 individuals of D. trimaculatus) were examined for parasites. The results identified 5 species of parasitic helminth: Haliotrema sp., Hysterolecitha nahaensis, Bivesicula sp., Hysterothylacium sp. and Contracaecum sp.. Of these, one species was found in the gills (Haliotrema sp.), two species (Hysterolecitha nahaensis, Bivesicula sp.) in the stomach and two species (Hysterothylacium sp., Contracaecum sp.) in the gut. Infested prevalence of Haliotrema sp. on D. trimaculatus was highest (70%) and prevalence of Bivesicula sp. on D. reticulatus. was the lowest (0.6%).